(untitled) - Riches, William T. Martin (New York, 2004)
This completely revised and updated edition of a popular text focuses on the African American struggle for civil rights from 1945-2002. William T. Martin Riches shows how the black community used the institutions created byde juresegregation to overcome apartheid and white resistance. Riches emphasises their influence on other groups demanding justice in America and warns that recent events and administrations have endangered the gains made by the movement.
Keywords: African Americans,Civil rights movements,United States; Civil rights,History,United States,History,Race relations; 20th century,20th century